Transformational Leadership of School Principals At The Muhammadiyah Junior High School Level In Wonosobo Regency - Muhammad Rasyid Ridho; Agri Novezar, Raga (Ittishal Educational Research Journal, 2024)
This research aims at finding out the principals’ leadership of SMP Muhammadiyah in Wonosobo Regency in implementing transformational leadership. It is a survei research using mixed- methods research approach of qualitative and quantitative with the principals of SMP Muhammadiyah in Wonosobo Regency as research subjects. This research used data collecting technique of observation, questionnaire with likert scale model, and unstructured interview. The data were analyzed with the formula of simple percentage, then described, and strengthened with the results of the observation and unstructured interview. The result of the research showed that the transformational leadership of SMP Muhammadiyah principals in Wonosobo Regency belongs to moderate category (74%), with detail as follows (1) the charisma belongs to high category (76%), (2) the individual awareness belongs to moderate category (73%), (3) the intellectual stimulus belongs to moderate category (74%), (4) the individual inspiration belongs to moderate category (70%), (5) the transformational leadership of the principal of SMP Muhammadiyah 1 Wonosobo belongs to high category (75.8%), (6) the transformational leadership of the principal of SMP Muhammadiyah 2 Sapuran belongs to moderate category (62.1%), (7) the transformational leadership of the principal of SMP Muhammadiyah 3 Leksono belongs to moderate category (63.1%), (8) the transformational leadership of the principal of SMP Muhammadiyah 4 Kertek belongs to moderate category (62.7%), (9) the transformational leadership of the principal of SMP Muhammadiyah 5 Kaliwiro belongs to moderate category (63.5%), (10) ) the transformational leadership of the principal of SMP Muhammadiyah 6 Tieng belongs to moderate category (60.6%).